Self-limited childhood epilepsies are disorders of the perisylvian communication system, carrying the risk of progress to epileptic encephalopathies—Critical review - Halász, Péter; Szũcs, Anna (Frontiers in Neurology, 2023)
We aimed to review the coherent spectrum (self-limited focal epilepsy with centrotemporal spikes, atypical Rolandic epilepsy and electrical status epilepticus in sleep) of self-limited focal epilepsies showing their spectral togetherness and discussing the debated topics. Our endeavor is to support the system epilepsy concept in this group of epilepsies, using them as models for epileptogenesis in general. The trans-spectral continuity of the involved conditions is evidenced by several features: language impairment; the shared presence of centrotemporal spikes and ripples (with changing electromorphology across the spectrum); the essential timely and spatial independence of interictal epileptic discharges from seizures; NREM sleep relatedness; and the existence of the intermediate severity ‘atypical’ form. These epilepsies might be the consequences of a genetically determined transitory developmental failure, reflected by early and widespread neuropsychological symptoms distinct from the secondary cognitive loss, caused by epilepsy itself. The involved epilepsies carry the risk to progress to severe, potentially irreversible encephalopathies.